Circulating health rumors in the 'Arab World': A 12-month content analysis of news stories and reader commentary about Middle East Respiratory Syndrome from two Middle Eastern news outlets. (August 2016) - Auter, Philip J; Douai, Aziz; Makady, Heidi; West, Chasah
The Internet provides great opportunity for news as well as entertainment. One such use is to keep abreast of public health concerns. As news outlets' websites give the audience the privilege of interacting and posting comments as an 'anonymous user' following the posted story, these initial comments trigger further comments—which can lead to speculation, rumor, and inaccurate information. The purpose of the current study was to compare one year of news and comments about the outbreak of Middle Eastern Respiratory Syndrome from two major Middle Eastern online news outlets from June 2013 to June 2014. All stories and reader comments about this topic were collected from Al Jazeera and Al-Arabiya and reviewed using framing analysis to determine their framing and approach to the outbreak. The research focused primarily on how discussion and rumor may spread through both the stories as well as the controversial commentary sections.